2022
DOI: 10.1097/hjh.0000000000003274
|View full text |Cite
|
Sign up to set email alerts
|

Cuffless blood pressure devices: the gap between patient acceptability and need for validation

Abstract: The PHE analysis showing an effect of sex on trends in salt intake determined by 24-h urine sodium measurements, and the report of Tan et al. on the performance of spot urine sodium measurements, raise the question: Is sex also a statistically significant factor influencing the downward trend in spot urine sodium concentrations reported by Tan et al. for the period of 2006-2014? Specifically, first, does a trend analysis of the spot urine sodium concentrations in women, like the trend analysis of 24-h urine so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The potential of cuffless devices seems superior to conventional out-of-office methods, such as ambulatory (ABPM) and home BP monitoring (HBPM), in their ability to provide a more complete BP profile. Furthermore, for users they are generally more comfortable to wear than cuff-based monitors, making them far more acceptable [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The potential of cuffless devices seems superior to conventional out-of-office methods, such as ambulatory (ABPM) and home BP monitoring (HBPM), in their ability to provide a more complete BP profile. Furthermore, for users they are generally more comfortable to wear than cuff-based monitors, making them far more acceptable [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Early studies compared 24-h intra-arterial and cuff-based ABPM, where both methods demonstrated a significant dipping of BP during the nighttime [1]. Although cuff-based ABPM is imperfect due to artifacts, movement [2], cuff issues, cost and patient acceptability [3], it is unanimously recommended by all major hypertension guidelines as the best available technique for the diagnosis and management of hypertension [4–6].…”
mentioning
confidence: 99%